2018
DOI: 10.1021/acscatal.8b01254
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Isolated Ga3+ Cations in Ga/H-MFI Prepared by Vapor-Phase Exchange of H-MFI Zeolite with GaCl3

Abstract: Ga/H-MFI was prepared by vapor-phase reaction of GaCl 3 with Brønsted acid O−H groups in dehydrated H-MFI zeolite. The resulting [GaCl 2 ] + cations in the as-exchanged zeolite are treated in H 2 at 823 K to stoichiometrically remove Cl ligands and form [GaH 2 ] + cations. Subsequent oxidation in O 2 and characterization by IR spectroscopy and NH 3 -temperature-programmed desorption (TPD) suggests that, for Ga/Al ratios ≤0.3, Ga 3+ exists predominantly as [Ga(OH) 2 ] + −H + cation pairs and to a lesser degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
216
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(231 citation statements)
references
References 84 publications
15
216
0
Order By: Relevance
“…42 For the application of these equations, rate coefficients (per Al tot atom) were normalized by the fraction of [GaH] 2+ cations per Al tot atom determined via NH 3 -TPD measurements (details described in the SI). 41 2.3. Theoretical Methods.…”
Section: Preparation Of H-mfi and Ga/h-mfi Nh 4 -Mfi (Zeolyst Cbv 3mentioning
confidence: 99%
See 1 more Smart Citation
“…42 For the application of these equations, rate coefficients (per Al tot atom) were normalized by the fraction of [GaH] 2+ cations per Al tot atom determined via NH 3 -TPD measurements (details described in the SI). 41 2.3. Theoretical Methods.…”
Section: Preparation Of H-mfi and Ga/h-mfi Nh 4 -Mfi (Zeolyst Cbv 3mentioning
confidence: 99%
“…Detailed characterization of these samples shows that for Ga/Al ratios below 0.3, and upon reduction under anhydrous conditions, all of the Ga is present as isolated [GaH] 2+ cations or as [GaH 2 ] + -H + cation pairs; neutral GaO x agglomerates are undetectable in these samples. 41…”
Section: Introductionmentioning
confidence: 99%
“…In a similar way, it was reported that [Ga(OH)H] + cations on zeolite undergo condensation with the proximate Brønsted acid protons to form [GaH] 2 + cations and one equivalent of H 2 O. [14] The divalent [GaH] 2 + cations show high activity for CÀ H activation of light alkane. [6c,19] This lead us to deduce that the [GaCH 3 ] 2 + may further react with CH 4 to form [Ga(CH 3 ) 2 ] + ( 13 C signal at ca.…”
Section: Chemcatchemmentioning
confidence: 68%
“…The formation of Ga-OH groups is reflected by the two weak signals at 0.9 and 1.4 ppm on Ga/ ZSM-5-redox ( Figure 4b), probably due to different types of Ga species. [8,14] It is interesting to note that the signal intensity of Ga-OH (0.9 ppm) is remarkably increased on Ga/ZSM-5-redox- 13 CH 4 , accompanied with a new signal at 0.1 ppm (Figure 4c). According to the 1 H chemical shift for metal methyl groups on zeolites, [11b,15] the Ga-CH 3 species is responsible for the 0.1 ppm signal.…”
Section: Methane Activationmentioning
confidence: 96%
“…[10] Hsieh and coworkers have shown that exchanging 8 % of the Brønsted acid sites of H-ZSM-5 increases the selectivity to aromatics from~15 % to~60 % during DHA of ethylene. [11] Cu-, Zn-, Ga-and Fe-exchanged zeolites are known to catalyze reactions such as the partial oxidation of methane to methanol, [12,13] dehydrogenation of light alkanes, [14][15][16][17] and decomposition of N 2 O to N 2 and O 2 , [18][19][20] respectively. Overall, these selected examples demonstrate that metal-exchanged zeolites offer the potential to convert readily available methane to value-added products.…”
Section: Introductionmentioning
confidence: 99%